Wild Sorghum as a Promising Resource for Crop Improvement - Ananda, Galaihalage K. S.; Myrans, Harry; Norton, Sally L.; Gleadow, Roslyn; Furtado, Agnelo; Henry, Robert J. (Frontiers in Plant Science, 2020)
Sorghum bicolor (L.) Moench is a multipurpose food crop which is ranked among the top five cereal crops in the world, and is used as a source of food, fodder, feed and fuel. The genus Sorghum consists of 26 diverse species. Cultivated sorghum was derived from the wild progenitor S. bicolor subsp. verticilliflorum, which is commonly distributed in Africa. Archeological evidence has identified regions in Sudan, Ethiopia and West Africa as centers of origin of sorghum, with evidence for more than one domestication event. The taxonomy of the genus is not fully resolved, with alternative classifications that should be resolved by further molecular analysis. Sorghum is known as “the camel amongst the crops” due to its ability to withstand severe droughts which makes it suitable to grow in regions where other major crops cannot be grown. Wild relatives of many crops have played significant roles as genetic resources for crop improvement. Although there have been many studies of domesticated sorghum, few studies have reported on its wild relatives. In Sorghum, some species are widely distributed while others are very restricted. Of the 17 native sorghum species found in Australia, none have been cultivated. Isolation of these wild species from domesticated crops makes them a highly valuable system for studying the evolution of adaptive traits such as biotic and abiotic stress tolerance. The diversity of the genus Sorghum has probably arisen as a result of the extensive variability of the habitats over which they are distributed. The wild genepool of sorghum may, therefore, harbor many useful genes for abiotic and biotic stress tolerance. While there are many examples of successful examples of introgression of novel alleles from the wild relatives of other species from Poaceae, such as rice, wheat, maize and sugarcane, studies of introgression from wild sorghum are limited. An improved understanding of wild sorghums will better allow us to exploit this previously underutilized genepool for the production of more resilient crops.